Solving for X in this equation would be as follows:

1. Move all terms to the left side and set equal to zero.
2. Now set each factor equal to zero.

x = 10,-22

To find the value of (x+6)(x+6) = 256, you first need to simplify the left hand side of the equation:

(x+6)(x+6) = x2 +6x +6x + 36 = x2 + 12x + 36

Substituting this to the original equation will give you this x2 + 12x + 36 = 256, which can further be simplified by moving all terms to the left. Doing that will give you the quadratic form (ax2 + b2 + c = 0) of the equation:

x2 + 12x - 220 = 0

Remember that the roots can be obtained by using the quadratic formula given by:

x = [(-b)±√b2-(4ac)] / 2a where a, b, c are the coefficients of the equation. That is, a = 1, b = 12 and c = -220

Substituting the values will give you:

x = [-(12)±√(12)2-(4*1*-220)] / 2(1)

x = [-12±√144-(-880)] / 2

x = [-12±√1024] / 2

x = [-12±32] / 2

First root now equals to:
x = [-12+32] / 2
x = 10

Second root:
x = [-12-32] / 2
x = -22

There you have it. The values of x are 10 and -22.

by 9 40 75
(x+6)(x+6)=256

take sqr root of each side

x+6=16

x= 16 - 6

x= 10

x+6= -16

x=  -16 -6

x= -22

we find two answers x= 10  and  x= -22

`
by 1 2

The Value of x in the equation (x+6)(x+6)=256

(x+6)(x+6)=256

X2+6x+6x+36=256

X2+12X+36=256

(X+6)2=256 {(a+b)2=a2+2ab+b2}

X+6=16 (take sqr root)

X=16-6

X=10

Ans: X=10

by 1 7
(X+6)(X+6)=256

(X+6)^2=256

(X+6)= 256^(1/2)

X+6=+16

X=22

And

X+6=-16

X=-10

You can also solve by making the quadratic equation and solve for that equation.
Any square root have a two solution
by 2 5

let assume t = x+6

(x+6)(x+6) = 256 => t*t = 256

t2  = 256

t    =  + or - 16

x + 6 = +16 => x = 10   and x + 6 = -16 => x = -22

x have two values +10 and -22

by 1

Hi!

I have explained the answer in details with step by step procedure as an image file. I think this must help to you to understand clearly.

by 3

Simple approach to solve this :

(x+6)(x+6)=256

(x+6)2 = 256

(x+6)2 = 162

therefore, (x+6) = 16 or (x+6) = -16

Let's solve x+6=16

=> x = 16-6 =10

Now, Lets solve x+6=-16

=>x= -16-6 = -22

therefore x = 10 ,-22 for given equation!!

by 2